Persistent luminescence of Eu/Dy-doped Sr2MgSi2O7 glass-ceramics processed by aerodynamic levitation. Issue 16 (December 2022) - Fernández-Rodríguez, L.; Allix, M.; Gorni, G.; Canizarès, A.; Ory, S.; Mather, G.C.; Durán, A.; Levy, D.; Pascual, M.J.
Abstract: Glass beads of the Sr2 MgSi2 O7 stoichiometric composition and a non-stoichiometric composition with higher SiO2 /SrO ratio doped with Eu2 O3 /Dy2 O3 were prepared through aerodynamic levitation coupled to CO2 laser heating. The glass beads were subsequently treated at 1100 ºC to produce glass-ceramics with Sr2 MgSi2 O7 : Eu 2+, Dy 3+ as the main crystalline phase. The doped glasses exhibit red emissions; after crystallisation, the corresponding glass-ceramics emit blue light under UV excitation. The starting glass composition considerably affects the crystallisation process, resulting in Sr2 MgSi2 O7 glass-ceramics with very different microstructures which, in turn, have a significant influence on the luminescence properties. The photoluminescence emission spectra of the glass-ceramics under UV light show a broadband emission (λ = 400–500 nm) with a main peak assigned to the typical Eu 2+ transition under excitation at 365 nm. Both the intensity of the emission and the persistence time significatively increase on decreasing temperature. Glass-ceramics from the non-stoichimetric glass composition co-doped with 1Eu2 O3 /0.5Dy2 O3 (mol%.) provided the longest persistence times.